MOLECULAR IDENTIFICATION OF PHOSPHATE SOLUBILIZING BACTERIA FROM PGPR PRODUCT DERIVED FROM TEMANGGUNG REGENCY - Muhammad Falih Akbar; Susiana Purwantisari; Sri Pujiyanto; Rejeki Siti Ferniah (BRIN - Badan Riset dan Inovasi Nasional, 2023)
T Phosphate solubilizing bacteria are soil bacteria that can dissolve phosphates from insoluble phosphate bonds so that they can be absorbed by plants. Phosphates in the soil are naturally present in organic and inorganic forms. Both forms are insoluble or slightly soluble forms of phosphate, so their availability for soil biota is very limited. This study aimed to identify the phosphate solubilizing bacteria from locally PGPR product from Temanggung, Indonesia, namely BPF 1. The method in this study was carried out by molecular identification using the 16S rRNA encoding gene which includes bacterial DNA isolation, DNA amplification using PCR, bacterial DNA sequencing and the creation of phylogenetic trees. The results of the study were obtained isolate bacteria solubilizing phosphate BPF 1 from PGPR products of local farmers of Temanggung Regency identified as the genus Bacillus, having the closest kinship with B. subtilis strain SBMP4 (NR_118383.1) with a similarity of 98.42%.